Report on the Short Endoscopic Exocrine Pancreatic Function Test in Children and Young Adults. Issue 5 (May 2020) - Mehta, Devendra I.; He, Zhaoping; Bornstein, Jeffrey; Molle-Rios, Zarela; Conwell, Darwin L.; Horvath, Karoly
Abstract : Objectives: Endoscopic pancreatic function test (ePFT) has been in use for exocrine function testing since the 1990s. In patients, short ePFT assesses acinar function, unlike the longer version for ductal function in adults. The present study summarizes characteristics of 1913 short ePFTs (S-ePFT) performed at 2 centers since 2001. Methods: The main indications in patients presenting at ages infancy to 24.3 years, for the S-ePFT were failure to thrive, weight loss, diarrhea, and abdominal pain with bloating. Secretin was administered as bolus, and 4 aliquots of fluid were collected between 4 and 10 minutes after administration. Amylase, lipase, trypsin, and chymotrypsin activities were measured in the laboratory. Results: The pH of consecutive samples increased by 0.3 to 0.7. Overall, 36.7% had abnormal S-ePFT with selective amylase deficiency (9.5%) and generalized enzyme deficiency (8.9%) being the most frequent. Retest reproducibility, repeatability, and clinical validity were high. By adding S-ePFT to endoscopy for the suspicion of malabsorption, the abnormal findings increased by 36.9%. Conclusions: Short ePFT assesses pancreatic acinar function in a reliable and clinically meaningful way in patients. Diagnostic yield of endoscopy increased substantially albeit with increased sedation time. By S-ePFT ductal function, cytokines and proteomics can also be assessed.